Improving Qur’anic Literacy of Indonesian Diaspora Students in Medina through International Community Service of Universitas Muhammadiyah Sumatera Utara Students - Sinulingga, Rajesta; Rahman, Abd (Universitas Pahlawan Tuanku Tambusai, 2026)
Correct Qur’anic reading is a foundational religious obligation for Muslim children and a key element in character formation, particularly within diaspora contexts where access to structured religious education is limited. While studies on Qur’anic literacy are well established, empirical research examining the pedagogical contribution of university students to Qur’anic learning among Indonesian diaspora children in the Middle East remains scarce. This study addresses this gap by analyzing the role of KKNI students from the Faculty of Islamic Studies, Universitas Muhammadiyah North Sumatra, in enhancing the Qur’an reading skills of fourth-grade Indonesian diaspora students in Madinah. Employing a qualitative descriptive approach, data were gathered through classroom observations, semi-structured interviews, reading performance assessments, and documentation. The findings indicate that structured mentoring, the application of the talaqqi method, and sustained motivational support contributed to measurable improvements in reading fluency, accuracy of makharijul huruf, and adherence to tajwid rules. These results highlight the strategic function of KKNI students not merely as instructional assistants but as facilitators of context-sensitive Qur’anic learning. The study concludes that university student engagement can play a significant role in strengthening Qur’anic literacy and religious character development among Indonesian diaspora learners.